Comparative simulation analysis of the economics of unit commitment to determine the cost of supplying electricity in simple generating systems in the Bengkulu region - Yunus, Rahmat Fadillah; Adi, Tri Wahyu (Universitas Negeri Padang, 2025)
An efficient electrical system is essential to meet the energy needs of the community without incurring high operational costs. This study aims to compare the total operational costs of power plants during three extreme time periods: low load (00:00–05:00), medium load (06:00–18:00), and high load (19:00–23:00), and to determine the most efficient combination of power plants using the Unit Commitment (UC) method based on priority list techniques. The study was conducted on the Bengkulu regional power system with the assumption of zero startup costs due to data limitations. Simulation results show that coal-fired power plants (IPP), hydroelectric power plants, and micro-hydro power plants serve as the base load power plants that are always active due to their low operational costs, while diesel power plants are only used as supplements when load exceeds the capacity of the main power plants. The lowest total operational cost occurs during low-load periods at Rp 40,936,446/hour, while the highest cost occurs during peak-load periods at Rp 65,040,329/hour. This finding confirms that optimizing the combination of power plants based on cost efficiency can significantly reduce operational expenses. In the future, it is expected that the electricity system can adopt smart grid technology to reduce, even eliminate, the use of inefficient diesel power plants.